The Second Infantry Division in World War I a history of the American Expeditionary Force regulars, 1917 - 1919 - Clark, George B. (McFarland, 2007)
"This volume details the fighting experiences of the Second Division, from its creation in the fall of 1917 through 1919. Appendices provide information regarding the pedigree of the division and its units; a syllabi of the Second Division's experiences; and a list of major awards received by Second Division personnel. Detailed maps and period photographs are also included"--Provided by publisher.
Keywords: United States. -- Army. -- Division, 2nd; USA -- American Expeditionary Forces; Weltkrieg (1914-1918); World War, 1914-1918 -- Campaigns -- France; World War, 1914-1918 -- Regimental histories -- United States; Frankreich; USA